Molecular Profiling of Appendiceal Epithelial Tumors Using Massively Parallel Sequencing to Identify Somatic Mutations. (1st July 2014) - Liu, Xiaoying; Mody, Kabir; de Abreu, Francine B; Pipas, J Marc; Peterson, Jason D; Gallagher, Torrey L; Suriawinata, Arief A; Ripple, Gregory H; Hourdequin, Kathryn C; Smith, Kerrington D; Barth, Richard J; Colacchio, Thomas A; et al.
Abstract: BACKGROUND: Some epithelial neoplasms of the appendix, including low-grade appendiceal mucinous neoplasm and adenocarcinoma, can result in pseudomyxoma peritonei (PMP). Little is known about the mutational spectra of these tumor types and whether mutations may be of clinical significance with respect to therapeutic selection. In this study, we identified somatic mutations using the Ion Torrent AmpliSeq Cancer Hotspot Panel v2. METHODS: Specimens consisted of 3 nonneoplastic retention cysts/mucocele, 15 low-grade mucinous neoplasms (LAMNs), 8 low-grade/well-differentiated mucinous adenocarcinomas with pseudomyxoma peritonei, and 12 adenocarcinomas with/without goblet cell/signet ring cell features. Barcoded libraries were prepared from up to 10 ng of extracted DNA and multiplexed on single 318 chips for sequencing. Data analysis was performed using Golden Helix SVS. Variants that remained after the analysis pipeline were individually interrogated using the Integrative Genomics Viewer. RESULTS: A single Janus kinase 3 ( JAK3 ) mutation was detected in the mucocele group. Eight mutations were identified in the V-Ki-ras2 Kirsten rat sarcoma viral oncogene homolog ( KRAS ) and GNAS complex locus ( GNAS ) genes among LAMN samples. Additional gene mutations were identified in the AKT1 (v-akt murine thymoma viral oncogene homolog 1), APC (adenomatous polyposis coli), JAK3, MET (met proto-oncogene), phosphatidylinositol-4, 5-bisphosphate 3-kinase ( PIK3CA ), RB1 (retinoblastoma 1), STK11 (serine/threonine kinase 11), and tumor protein p53 ( TP53 ) genes. Among the PMPs, 6 mutations were detected in the KRAS gene and also in the GNAS, TP53, and RB1 genes. Appendiceal cancers showed mutations in the APC, ATM (ataxia telangiectasia mutated), KRAS, IDH1 [isocitrate dehydrogenase 1 (NADP+)], NRAS [neuroblastoma RAS viral (v-ras) oncogene homolog], PIK3CA, SMAD4 (SMAD family member 4), and TP53 genes. CONCLUSIONS: Our results suggest molecular heterogeneity among epithelial tumors of the appendix. Next generation sequencing efforts have identified mutational spectra in several subtypes of these tumors that may suggest a phenotypic heterogeneity showing mutations that are relevant for targeted therapies.